2016
DOI: 10.1021/acs.est.6b01301
|View full text |Cite
|
Sign up to set email alerts
|

How Biotransformation Influences Toxicokinetics of Azole Fungicides in the Aquatic Invertebrate Gammarus pulex

Abstract: Biotransformation is a key process that can greatly influence the bioaccumulation potential and toxicity of organic compounds. In this study, biotransformation of seven frequently used azole fungicides (triazoles: cyproconazole, epoxiconazole, fluconazole, propiconazole, tebuconazole and imidazoles: ketoconazole, prochloraz) was investigated in the aquatic invertebrate Gammarus pulex in a 24 h exposure experiment. Additionally, temporal trends of the whole body internal concentrations of epoxiconazole, prochlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 69 publications
4
66
0
Order By: Relevance
“…As the data suggests, factors other than hydrophobicity may be important in accumulation, such as biotransformation, which could also partly explain the variability in BCFs. Authors have demonstrated that G. pulex are able to metabolise a range of organic micropollutants (Ashauer et al., 2012, Jeon et al., 2013b, Rösch et al., 2016). Conservation of cytochrome P450 enzymes has also been observed in invertebrates (Snyder, 2000) and pharmaceuticals have been shown to undergo oxidative and conjugation reactions (Jeon et al., 2013b).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As the data suggests, factors other than hydrophobicity may be important in accumulation, such as biotransformation, which could also partly explain the variability in BCFs. Authors have demonstrated that G. pulex are able to metabolise a range of organic micropollutants (Ashauer et al., 2012, Jeon et al., 2013b, Rösch et al., 2016). Conservation of cytochrome P450 enzymes has also been observed in invertebrates (Snyder, 2000) and pharmaceuticals have been shown to undergo oxidative and conjugation reactions (Jeon et al., 2013b).…”
Section: Resultsmentioning
confidence: 99%
“…For biocides (algicides), glutathione conjugates have been detected in G. pulex and D. magna (Jeon et al., 2013b). Finally, G. pulex have also been shown to biotransform azole fungicides into sulphate, glutathione and glucose-sulphate conjugates (Rösch et al., 2016). Human trials show that the major biotransformation products of propranolol were HP and napthoxylactic acid (Walle and Gaffney, 1972).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations